Analisis Komitmen Organisasi Pada Wisata Arum Jeram PT. Lintas Jeram Nusantara Sukabumi (Survey Pada PT. Lintas Jeram Nusantara) - Deden Wawi (Journal of Economic, Bussines and Accounting (COSTING), 2022)
Knowing the analisys and problems that occur in the company about how much influence organizational commitment has on the company PT Lintas Jeram Nusantara. This study aims to analyze the development of organizational commitment and analyze a constraint and obstacles to development and organizational commitment at PT. Cross Archipelago Rapids. The research method used in this research is a qualitative research method. Qualitative research methods are also called naturalistic research methods because research is carried out in natural conditions. The results of this study have no significant effect on organizational commitment. The results of this study will be used as material for further studies with more in-depth matters. In addition, as a contribution of knowledge that researchers have about the analysis of organizational commitment. Keywords: Organizational Commitment, white water rafting, journal